Visualizing the formation of the Kondo lattice and the hidden order in URu2Si2 - Aynajian, Pegor; da Silva Neto, Eduardo H.; Parker, Colin V.; Huang, Yingkai; Pasupathy, Abhay; Mydosh, John; Yazdani, Ali (Proceedings of the National Academy of Sciences - PNAS, 2010)
Heavy electronic states originating from the f atomic orbitals underlie a rich variety of quantum phases of matter. We use atomic scale imaging and spectroscopy with the scanning tunneling microscope to examine the novel electronic states that emerge from the uranium f states in URu 2 Si 2 . We find that, as the temperature is lowered, partial screening of the f electrons’ spins gives rise to a spatially modulated Kondo–Fano resonance that is maximal between the surface U atoms. At T  = 17.5 K, URu 2 Si 2 is known to undergo a second-order phase transition from the Kondo lattice state into a phase with a hidden order parameter. From tunneling spectroscopy, we identify a spatially modulated, bias-asymmetric energy gap with a mean-field temperature dependence that develops in the hidden order state. Spectroscopic imaging further reveals a spatial correlation between the hidden order gap and the Kondo resonance, suggesting that the two phenomena involve the same electronic states.